Liderança feminina no ambiente fabril: estudo de caso em uma empresa do Polo Industrial de Manaus - Souza, Raquel Castro de (Brasil, 2024)
The female trajectory is marked by overcoming stereotypes and gradually gaining space in the job market and in leadership positions. Despite the advances, challenges such as low representation in senior management positions and the perpetuation of gender biases still limit equality. The general objective of this study was to investigate the challenges faced by women in leadership positions in a factory located in the Manaus Industrial Complex. The option for data collection was through a qualitative approach, based on semi-structured interviews with eight leaders who work in a company in the Manaus Industrial Complex, whose excerpts from the interviews were analyzed through Content Analysis. The results obtained indicate that the main challenges are related to conflict management, adjusting communication to the individualities of subordinates and resistance to female leadership, despite the inclusion policies adopted by the company. The content of this material reveals emotional skills and adaptability as important competencies to overcome these challenges.